Extreme Make Over: Disposition Development of Pre-Service Teachers - Tynisha Meidl; Beth Baumann (The University of Alabama, 2022)
Pre-service teachers are on an educational and professional journey in which they are trying to figure out the "right stuff" needed to be an effective teacher while being a "student." Many pre-service teachers engage in community service projects, yet it is unclear how these experiences inform the dispositional development of pre-service teachers. In this study, the authors examined the outcomes of a community service experience pre-service teachers (n = 20) participated in as part of the [student group]. The authors present the results of a qualitative study. Findings suggest pre-service teachers realize the multiplicities of student needs in an authentic setting and the potential disconnect between what is learned during one's teacher education undergraduate program and the realities of being a teacher once employed as a classroom teacher. The authors conclude with reflections on the importance of having concrete ways for pre-service teachers to develop dispositions beyond the course-based field experiences and student teaching.